EAD no cárcere: aspirações sobre essa modalidade de ensino no Presídio Estadual Metropolitano III (PEM III) - BARROS, Caio Cesar Carmo (2022)
This Course Completion Work (TCC) entitled "EAD NO CÁRCERE: aspirations for this type of education in the Metropolitan State Prison III - PEM III" arose from the question: What contributions and possibilities to implement Distance Education (DE) in the Prison Metropolitan State III, known as PEM III? Its general objective was to analyze contributions and possibilities of implementing Distance Education (DE) in the Metropolitan State Prison III, based on the conception of education professionals (teachers and pedagogical coordinators). And, the specific ones were: to know the process of Formal Teaching developed by the State Secretariat of Penitentiary Administration of the State of Pará (SEAP); investigate the possibilities of implementing distance education education in the Prison System; and, identify methodological strategies that Mathematics teachers can develop in distance education in PEM III. This is a field study with a qualitative approach, the results of which show that distance education teaching is a type of teaching that is well regarded by teachers who work in that space, according to which there is a need for monitors in the classroom to clear up doubts. of detained students. It was revealed that education in the Prison System of Pará only advanced from 2006 onwards, with the approval of the Educating for Freedom Project, which aimed to guarantee the access of PESRPL to education. It was also evident that distance education is not a reality in all prisons in Pará, and that it is a necessity for both detainees and education professionals who work there.